The Phenomenon of Fake News (Hoax) in Mass Communication: Causes, Impacts, and Solutions - M, Deddy Satria; Hairunnisa (HM Publisher, 2023)
challenge faced in the digital era. The spread of fake news can have detrimental effects, such as disrupting public opinion, influencing democratic processes, creating social chaos, and damaging the reputation of individuals or organizations. The main causes for the emergence of fake news include technological factors, political motivation, economic gain, ignorance or lack of media literacy, and psychological factors such as the need for validation or sensation. Advances in technology and social media have accelerated the spread of fake news and complicated efforts to contain it. It is important to tackle the fake news phenomenon with a holistic approach. This involves the active role of individuals, news organizations, journalists, social media platforms, government agencies, and society as a whole. Increasing media literacy, accurate verification of facts, ethical journalism, cooperation with social media platforms, proper regulation, and prompt response to fake news are important steps in dealing with this phenomenon. The impact of fake news is very detrimental and can disrupt social stability, public trust, and information integrity. Therefore, collective efforts and awareness of the importance of fighting fake news are very important in building a healthy and trustworthy mass communication environment.